Altered Ghrelin Secretion Pattern and Sense of Hunger by Providing Low and High Density Breakfast in Obese Female Adolescents - Ni Luh Putu Ayu Putrisari Putri; Elyana Asnar; Purwo Sri Rejeki (Biomolecular and Health Science Journal, 2018)
Introduction: Ghrelin has been recognized to have a major influence on energy balance. Hence, the discovery of various regulatory factors that control ghrelin secretion may have major implications for the development of drugs and diet control. This study aims to analyze differences in ghrelin secretion pattern and prevention of hunger in the provision of breakfast in low-calorie breakfast, low energy density and high energy density in obese female adolescents.Methods: Subjects were female students aged 18-22 years with a BMI=25 kg/m², receiving low-calorie breakfast with low (n=8) and high energy density (n=8). Before the breakfast, subjects fasted for 12 hours and were subjected to plasma ghrelin level and hunger measurement using visual analog scale (VAS). Breakfast was done at 08.00, divided into three parts and each was taken for 5 minutes. Measurement of plasma ghrelin was carried out again post prandial (PP) at 2 hours and 4 hours. VAS filling was done 1 hour PP, 2 hours PP, 3 hours PP, and 4 hours PP.Result: There were differences in plasma ghrelin level, but not significant. VAS 1 analysis of hunger (p=0.040) at 4 hours PP and VAS 3 of satiety (p=0.025) was significantly different at 3 hours PP. Conclusion: Food density did not affect the plasma ghrelin levels. Low density foods are more effective to prevent hunger in 4 hours PP and increases satiety in 3 hours PP.